The transitional dynamics of fiscal policy in small open economies - Ben J. Heijdra; Jenny E. Ligthart (Center for Economic Studies and ifo Institute (CESifo), 2006)
The paper studies the dynamic macroeconomic effects of fiscal shocks of various duration (permanent and temporary) under different financing methods (lump-sum tax and government debt). To this end, we develop an intertemporal macroeconomic model for a small open economy, featuring monopolistic competition in the intermediate goods market, endogenous (intertemporal) labor supply, and finitely lived households. Endogenous labor supply is crucial in generating cyclical adjustment paths and yields faster convergence to the new steady state compared with exogenous labor supply. The quantitative output effects and transitional dynamics of fiscal policy differ substantially from those of an infinitely lived representative agent model. In addition, government debt is key in making the timing of shocks matter, thus yielding permanent output effects of temporary fiscal shocks.
Keywords: E12; E63; L16; 330